2018
DOI: 10.1080/21505594.2018.1499378
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Aggregatibacter actinomycetemcomitans secretin HofQ and host cytokines indicate a link between natural competence and interleukin-8 uptake

Abstract: Naturally competent bacteria acquire DNA from their surroundings to survive in nutrient-poor environments and incorporate DNA into their genomes as new genes for improved survival. The secretin HofQ from the oral pathogen Aggregatibacter actinomycetemcomitans has been associated with DNA uptake. Cytokine sequestering is a potential virulence mechanism in various bacteria and may modulate both host defense and bacterial physiology. The objective of this study was to elucidate a possible connection between natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…After challenge with the A. actinomycetemcomitans biofilm, the levels of CXCL1, CXCL8, and CCL2 were lower than in the control (Figure ). Previously, it was found that A. actinomycetemcomitans can sense and bind cytokines; among them was CXCL8 (T. Ahlstrand et al, ; T. Ahlstrand et al, ; T. Ahlstrand, Kovesjoki, Maula, Oscarsson, & Ihalin, ). Lower metabolic activity of biofilms induced by cytokine binding could lead to higher resistance (A. Paino et al, ) and could reduce the production of virulence factors providing an explanation why the peri‐implant mucosa was not impaired after challenge with the A. actinomycetemcomitans biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…After challenge with the A. actinomycetemcomitans biofilm, the levels of CXCL1, CXCL8, and CCL2 were lower than in the control (Figure ). Previously, it was found that A. actinomycetemcomitans can sense and bind cytokines; among them was CXCL8 (T. Ahlstrand et al, ; T. Ahlstrand et al, ; T. Ahlstrand, Kovesjoki, Maula, Oscarsson, & Ihalin, ). Lower metabolic activity of biofilms induced by cytokine binding could lead to higher resistance (A. Paino et al, ) and could reduce the production of virulence factors providing an explanation why the peri‐implant mucosa was not impaired after challenge with the A. actinomycetemcomitans biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the O-antigen part of A. actinomycetemcomitans LPS may mediate direct adhesion to abiotic surfaces [7]. Besides abiotic surfaces, A. actinomycetemcomitans LPS interacts with host molecules, such as human hemoglobin [129] and IL-8 [136], which may facilitate the iron acquisition and disturbance of host defense, respectively.…”
Section: The Virulence Properties Of a Actinomycetemcomitans Lipopolmentioning
confidence: 99%
“…actinomycetemcomitans is one of the human pathogens that is able to bind host cytokines, such as IL-1β, IL-8, and IL-6 [137,138], and internalize them [138,139], which leads to changes in the properties of biofilm, decreasing the metabolic activity [139], and changing the composition of the extracellular matrix [136,138]. Several potential bacterial proteins that may interact with human cytokines have been identified in A. actinomyctemcomitans, including intracellular ATP synthase subunit β [139], histone like DNA binding protein HU [139], and outer membrane proteins bacterial interleukin receptor I (BilRI) [138,140] and secretin channel HofQ [136]. The majority of these proteins have other functions in the bacterial cell related to metabolism, gene regulation, and uptake of nutrients and DNA for horizontal gene transfer, a character of so called "moonlighting" bacterial proteins [1].…”
Section: Sensing Of Host Signal Moleculesmentioning
confidence: 99%
“…To study the interactions of mature BilRI with a human macrophage cell line, the bilRI gene was cloned into the pET-15b vector (Novagen), and the recombinant protein was produced as described previously [ 24 ]. Since we aimed to use the mature form of BilRI without any tags or lipid components, after binding to a 5-ml HisTrap HP (GE Healthcare, Uppsala, Sweden) column [ 36 ], recombinant BilRI containing an N-terminal 6-histidine tag was digested with 200 NIH units of thrombin (MP Biomedicals, Santa Ana, CA, USA) at room temperature overnight. The released BilRI was eluted with binding buffer (20 mM NaH 2 PO 4 /Na 2 HPO 4 , 800 mM NaCl, 20 mM imidazole, pH 7.5), and purification was continued with size exclusion chromatography as described for His-tagged BilRI [ 36 ].…”
Section: Production and Purification Of Recombinant Bilrimentioning
confidence: 99%
“…Human venous blood was collected as described previously [ 36 ] from A. actinomycetemcomitans -positive adult periodontitis patients (21) and healthy controls (13) who provided written informed consent. Collection was conducted by a laboratory nurse at the Community Dental Health Care Center of Turku (Institute of Dentistry, University of Turku) or by a physician at the Unit for Specialized Oral Care in the Helsinki Metropolitan Area and Kirkkonummi (Helsinki, Finland).…”
Section: Human Serum Collectionmentioning
confidence: 99%